1980
DOI: 10.1203/00006450-198004000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Glucocorticoid in Unplanned Premature Labor. Controlled Study on the Effects of Betamethasone Phosphate on the Phospholipids of the Gastric Aspirate and on the Adrenal Cortical Function of the Newborn Infant

Abstract: SummaryThe effects of betamethasone on surfactant composition and neonatal adrenal function were compared with placebo in a doubleblid study, which included 74 patients at risk for premature delivery. The overall incidence of respiratory distress syndrome was low, and no difference was observed between the betamethasone and placebo groups. The phospholipid pattern (lecithin/sphingomyellin ratio, acetone precipitated lecithin, pbosphatidylinositol/sphingomyelin ratio, and phosphatidylglycerol/sphingomyelin rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…44,45 In the current study, nearly all infants were exposed to antenatal glucocorticoid. The timing of antenatal glucocorticoid therapy in relation to delivery had no statistically significant effect on the basal or stimulated cortisol levels soon after birth, which can be explained by the small sample size and/or the timing of the antenatal steroids.…”
Section: Discussionmentioning
confidence: 96%
“…44,45 In the current study, nearly all infants were exposed to antenatal glucocorticoid. The timing of antenatal glucocorticoid therapy in relation to delivery had no statistically significant effect on the basal or stimulated cortisol levels soon after birth, which can be explained by the small sample size and/or the timing of the antenatal steroids.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous randomized, controlled trails confirm the efficacy of this therapy [8, 38], and organizations such as the National Institutes of Health and the American College of Obstetricians and Gynecologists have recommended antenatal GC treatment for women at risk for delivery before 34 weeks of gestation [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Based on the works of Teramo 22 and Dorr 24 and their colleagues, it is not surprising that this study found that corticosteroid treatment, as reported on the newborn screening card, did not suppress 17-OHP levels. In fact, corticosteroid-exposed newborns were more likely than unexposed newborns to have higher 17-OHP levels.…”
Section: Commentmentioning
confidence: 99%
“…These differences often have not been significant, particularly after being corrected for multiple variables. 20,21 Teramo et al 22 compared the serum cortisol levels of 24-hour-old newborns who had been treated prenatally with betamethasone with those of newborns treated with placebo. There was no difference between cortisol levels in the groups, indicating that use of betamethasone did not have a sustained effect on fetal cortisol concentration.…”
Section: Commentmentioning
confidence: 99%